Effect of environmental conditions on the failure mechanisms and energy absorption of open-section crush elements under quasi-static loading. (1st February 2019) - Joosten, M.W.; Hirth, C.; Thomson, R.; Koerber, H.
Abstract: This paper presents the quasi-static energy absorption of open section monolithic carbon-epoxy specimens for a range of environmental test conditions. Experimental observations showed that the test temperature influenced the failure mode; elevated temperatures (>23 °C) resulted in the specimens exhibiting a splaying failure mode whilst reduced test temperature (−35 °C) resulted in a brittle failure mode. Despite the difference in failure modes, the reduced and elevated test conditions both resulted in lower energy absorption compared with the baseline result at ambient temperature. In addition to the temperature effect, introducing moisture further reduced the energy absorption. The results show that an un-conditioned specimen tested at ambient temperature may not necessarily represent the worst case and care must be taken when using ambient temperature tests to inform the design of crashworthy structures and the influence of environment should be accounted for during the design phase.